2006
DOI: 10.1242/jeb.02520
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cocaine effects on learning, memory and extinction in the pond snail Lymnaea stagnalis

Abstract: SUMMARY The persistence of drug addiction suggests that drugs of abuse enhance learning and/or impair extinction of the drug memory. We studied the effects of repeated cocaine on learning, memory and reinstatement in the pond snail, Lymnaea stagnalis. Respiratory behavior can be operantly conditioned and extinguished in Lymnaea, and this behavior is dependent on a critical dopamine neuron. We tested the hypothesis that repeated cocaine exposure promotes learning and memory or attenuates the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Alternatively, training in Meth may have activated downstream pathways within RPeD1 or other neurons that actively inhibit subsequent extinction learning. This result is similar to what we previously found for the effects of cocaine pre-exposure, in which reinstatement of operantly conditioned breathing behavior was enhanced compared with controls (Carter et al, 2006). In that study, however, animals were exposed for 5days to cocaine and then trained 3days after the last cocaine exposure.…”
Section: Effect Of Training In Meth On Extinction and Reinstatementsupporting
confidence: 91%
See 2 more Smart Citations
“…Alternatively, training in Meth may have activated downstream pathways within RPeD1 or other neurons that actively inhibit subsequent extinction learning. This result is similar to what we previously found for the effects of cocaine pre-exposure, in which reinstatement of operantly conditioned breathing behavior was enhanced compared with controls (Carter et al, 2006). In that study, however, animals were exposed for 5days to cocaine and then trained 3days after the last cocaine exposure.…”
Section: Effect Of Training In Meth On Extinction and Reinstatementsupporting
confidence: 91%
“…Based on our previous results with cocaine pre-treatment of snails (Carter et al, 2006) and previous work showing that psychostimulants enhance memory (see Introduction), we predicted that Meth used during initial training would enhance LTM such that extinction would be impaired and/or reinstatement would be greater than that in the Water control snails. Meth exposure during training diminished the extinction rate of the trained behavior.…”
Section: Effect Of Training In Meth On Extinction and Reinstatementmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated extinction in Lymnaea (McComb et al, 2002), and we further demonstrated that extinction can be extended or enhanced by a number of different means, including blocking newer memory formation (Sangha et al, 2003e;Sangha et al, 2005;Knezevic et al, 2011). Additionally, animals that have apparently forgotten exhibit re-instatement of the original training following a protocol that does not typically result in LTM formation (Sangha et al, 2003b;Carter et al, 2006;Parvez et al, 2006;Kennedy et al, 2010). We chose to assess the effects of (-)epicatechin (epi), as it has been identified as a bioactive molecule in vivo (Schroeter et al, 2006) and is also commonly consumed through cocoa, green tea, blueberries and red wine (Spencer, 2008).…”
Section: Introductionmentioning
confidence: 67%
“…First, we tested the impact of 5-HT because of previous work describing enhanced memory in Aplysia via changes in DNA methylation status (Rajasethupathy et al, 2012). Second, we previously reported that the psychostimulant drugs cocaine (Carter et al, 2006) and Meth (Kennedy et al, 2010) enhanced long-term memory (LTM) in snails. We also demonstrated that pre-exposure to Meth prior to weak training produced LTM of respiratory behavior that was not found in controls.…”
Section: Introductionmentioning
confidence: 99%